The Analysis Study of Histopathologic Diagnosis of Gastroesophageal Reflux Disease: An Anatomic Pathology Comprehensive Systematic Review - Prastyo, Wahyu Agus; Nugraheni, Artha Investari; Ayuningrum, Mutia Ruliana (The Indonesian Journal of General Medicine, 2024)
Introduction : This systematic review explores the histopathologic features of GERD and its differential diagnoses, emphasizing the role of endoscopic and histologic assessments in clinical practice. Methods : A systematic review was conducted following PRISMA 2020 guidelines to evaluate the histopathologic features of GERD and its differential diagnoses. Results : From an initial pool of 6006 publications, eight studies were identified as directly relevant after a thorough screening process. The findings highlight the importance of biopsy sampling and histologic evaluation in differentiating GERD from other esophageal inflammatory conditions. Key diagnostic features included basal cell hyperplasia, elongation of lamina propria papillae, and dilatation of intercellular spaces, which were critical for distinguishing GERD from other conditions. Conclusion : This systematic review emphasizes the importance of histopathologic evaluation in the accurate diagnosis of GERD and its differential diagnoses. Understanding the distinct histopathologic features of GERD, as well as technical aspects of biopsy sampling, is essential for improving diagnostic accuracy and preventing progression to severe complications.